On Cardiometabolic Risk Predictors: a Necessary Explanation - Raúl Cedeño Morales (Revista Finlay)
In recent years, it has grown reflection on what is the best anthropometric parameter for measuring overweight and obesity, which consistently stratify the risk for cardiovascular events and cause mortality.